Advanced imaging for quantification of abnormalities in the salivary glands of patients with primary Sjögren's syndrome. (21st November 2020) - Jimenez-Royo, Pilar; Bombardieri, Michele; Ciurtin, Coziana; Kostapanos, Michalis; Tappuni, Anwar R; Jordan, Natasha; Saleem, Azeem; Fuller, Teresa; Port, Kathleen; Pontarini, Elena; Lucchesi, Davide; Janiczek, Robert; et al.
Abstract: Objectives: To assess non-invasive imaging for detection and quantification of gland structure, inflammation and function in patients with primary Sjogren's syndrome (pSS) using PET-CT with 11 C-Methionine ( 11 C-MET; radiolabelled amino acid), and 18 F-fluorodeoxyglucose ( 18 F-FDG; glucose uptake marker), to assess protein synthesis and inflammation, respectively; multiparametric MRI evaluated salivary gland structural and physiological changes. Methods: In this imaging/clinical/histology comparative study (GSK study 203818; NCT02899377) patients with pSS and age- and sex-matched healthy volunteers underwent MRI of the salivary glands and 11 C-MET PET-CT. Patients also underwent 18 F-FDG PET-CT and labial salivary gland biopsies. Clinical and biomarker assessments were performed. Primary endpoints were semi-quantitative parameters of 11 C-MET and 18 F-FDG uptake in submandibular and parotid salivary glands and quantitative MRI measures of structure and inflammation. Clinical and minor salivary gland histological parameter correlations were explored. Results: Twelve patients with pSS and 13 healthy volunteers were included. Lower 11 C-MET uptake in parotid, submandibular and lacrimal glands, lower submandibular gland volume, higher MRI fat fraction, and lower pure diffusion in parotid and submandibular glands were observed in patients vs healthy volunteer, consistent with reduced synthetic function. Disease duration correlated positively with fat fraction and negatively with 11 C-MET and 18 F-FDG uptake, consistent with impaired function, inflammation and fatty replacement over time. Lacrimal gland 11 C-MET uptake positively correlated with tear flow in patients, and parotid gland 18 F-FDG uptake positively correlated with salivary gland CD20+ B-cell infiltration. Conclusion: Molecular imaging and MRI may be useful tools to non-invasively assess loss of glandular function, increased glandular inflammation and fat accumulation in pSS.